The association of physical activity against depression among Universiti Putra Malaysia undergraduate medical students-a cross sectional study - Lynncilla, Shakira; Koh, Eugene; Chong, Seng Choi (Universiti Putra Malaysia, 2024)
The crossroads of mental health and academia particularly in higher education have drawn consider- able attention. Research explores how physical activity impacts depression among medical students in higher educa- tion where mental health challenges are prevalent due to academic stress. Materials and methods: In an observation- al cross-sectional study, 251 undergraduate medical students participated by completing questionnaires assessing physical activity and depressive symptoms. The study utilized the International Physical Activity Questionnaire-Long Form and Centre for Epidemiologic Studies Depression Scale. Results: In a study of 251 medical students split into pre-clinical and clinical groups, the latter were older (23.2 vs 20.3 years) and generally had lower physical activity levels, especially in transport, domestic and leisure activities. Pre-clinical students showed higher overall activity. Depression levels differed significantly between groups with clinical student scoring higher (20.2 vs 18.7). Rela- tionships were noted between depression and physical activity, particularly in transport-related activities, walking and total physical activity-higher activity linked to lower depression. However, no significant correlation was found for moderate or vigorous physical activity levels. Conclusion: Study suggest promoting activities like walking and transportation to mitigate depression among medical students, offering strategies to enhance the mental well-being of future healthcare professionals.